Sangværket som udviklingsroman. Om Randi Habersaat Rodes bog Barneglad og engleklog - Auken, Sune (Grundtvig-Studier, 1999)
The Song-Work as Bildungsroman About Randi Habersaat Rode’s book Barneglad og engleklog (1996) By Sune Auken The article recognizes that with the book Barneglad og engleklog Randi Rode has made a significant contribution to Grundtvig research. The book is important for two reasons, partly because it is the first major work in literary scholarship on Grundtvig for a very long time, and partly because in its attempt to conceive of the first 146 hymns in Grundtvig’s Song-Work to the Danish Church as a coherent whole, it provides a thorough study of a text corpus which in previous Grundtvig scholarship has never been dealt with as a series of connected texts. At the same time, however, the article takes a doubtful look at the fundamental approaches in the book. Two features are questioned in the article: the method of the book and its treatment of the ma-terial. Barneglad og engleklog subscribes to the intertextual method which examines the connections between different texts, but the article argues that the book overlooks a series of important distinctions relating to intertextuality, and that consequently a number of the conclusions drawn in the book on the background of its method become dubious. Furthermore, the article questions the attempt made in the book to point out a sequential pattern in the first 146 hymns of the Song-Work to the Danish Church. A few of the interpretations contained in the book are taken up, and in each case it is concluded that the connections which Barneglad og engleklog professes to see are more than doubtful. The article concludes with regret that if the Song-Work to the Danish Church is carefully composed, that composition is different from the one presented in Barneglad og engleklog.